Do conventional foreign direct investment theories explain why multinational enterprises conduct foreign direct investment in Thailand? - Severn, Sean-Leigh (2007)
This study aims to determine if conventional foreign direct investment theories explain why multinational enterprises conduct foreign direct investment in Thailand. Theory testing based on multiple case studies will be the research method employed and qualitative secondary data will be used in an exploratory manner. Specifically, Dunning's eclectic paradigm will be tested against the foreign direct investment of three multinational enterprises in Thailand, namely, Royal Dutch Shell, Toyota and Tesco. The study shows that conventional foreign direct investment theories are not powerful enough to explain all of the reasons multinational enterprises conduct foreign direct investment in Thailand. Favorable exchange rates, weak market conditions, cultural similarities, geographic proximity, profitability, availability of partners, encouraging government incentives and the future potential of the region can play a substantial role when judging why multinational enterprises conduct foreign direct investment in Thailand. This enhances our understanding of foreign direct investment theories and highlights their shortcomings when applied to Thailand. Therefore, governments and business analysts should not only rely on conventional foreign direct investment theories in order to explain the foreign direct investment of multinational enterprises in Thailand.